Photo-Realistic 3D Models and Animations for Video Games and Films - Hosen, Md Saikat; Thaduri, Upendar Rao; Ballamudi, Venkata Koteswara Rao; Lal, Karu (Engineering International, 2021)
Realistic 3D objects are challenging to create. A detailed creation requires care if we can make remarkable detail and realism using techniques and a solid reference photo. In this post, we may learn how to construct beautiful, realistic scene objects using comprehensive procedures. This article shows how to use the Pen Tool and Blending Options to create a 3D animated scene. This work teaches simple Layer Styles to create beautiful shadows, lights, textures, and a realistic 3D feel. This work also shows how attractive illumination and rendering options may produce a natural scene. This article also shows how to make photo-realistic 3D models from digital images. This work teaches Illustrator pathways, texturing, essential lighting and rendering, texture application, and building and object parenting. This approach might even reconstruct tiny features or 3D items from 2D images. After a critical art stage, we can present the architecture of an animation design technique in this article. The goal is a conceptual and methodological lesson to approach this topic scientifically and practically. This goal also includes developing a scientifically sound paradigm to help comprehend realistic animation processes.
Keywords: Three Dimension; Animation; Modeling; Rendering; Keyframe; Games